(untitled) (Academicia Globe: Inderscience Research, 2025)
The article reveals the specifics and practical and methodological issues of assessing the value of non-residential commercial real estate, which is considered as the most effective method among the mechanisms of effective management of non-residential commercial real estate objects. Also, the approaches and methods used in assessing the value of real estate are described, and the factors affecting the value of non-residential commercial real estate objects are studied systematized.